2023
DOI: 10.3390/md21020055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characteristics of a Lectin from the Bivalve Glycymeris yessoensis

Abstract: C-type lectins (CTLs) are a family of carbohydrate-binding proteins that mediate multiple biological events, including adhesion between cells, the turnover of serum glycoproteins, and innate immune system reactions to prospective invaders. Here, we describe the cDNA cloning of lectin from the bivalve Glycymeris yessoensis (GYL), which encodes 161 amino acids and the C-type carbohydrate recognition domain (CRD) with EPN and WND motifs. The deduced amino acid sequence showed similarity to other CTLs. GYL is a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…In our previous study, the C-type lectins GYL and GYLman were identified from the hemolymph of mollusk G. yessoensis. They have a wide spectrum of microbial binding, including Gram-positive (Bacillus subtilis, Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli, Vibrio proteolyticus) and possibly participate in the immune defense of the G. yessoensis against bacterial attacks [24][25][26]. Considering the large number of bacteria in the aquatic environment, there should be other lectins to protect the mollusk from various pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, the C-type lectins GYL and GYLman were identified from the hemolymph of mollusk G. yessoensis. They have a wide spectrum of microbial binding, including Gram-positive (Bacillus subtilis, Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli, Vibrio proteolyticus) and possibly participate in the immune defense of the G. yessoensis against bacterial attacks [24][25][26]. Considering the large number of bacteria in the aquatic environment, there should be other lectins to protect the mollusk from various pathogens.…”
Section: Introductionmentioning
confidence: 99%